Pemberdayaan Perempuan dalam Penguatan Pengelolaan Bank Sampah Berbasis Digital di Karanggayam, Kalurahan Catur Tunggal, Sleman: Pengabdian - Arie Noor Rakhman; Fivry Wellda Maulana; Fajar Yulianto Prabowo; Muhammad Sholeh (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service program was carried out at the Wimalandaru Waste Bank in Karanggayam Hamlet, Catur Tunggal Village, Sleman, to improve waste management effectiveness through the implementation of a web-based waste bank application. The digital system implementation was able to address the partner’s main problems, particularly the inefficiency of manual record-keeping, limited structured data, and low community participation. Digitalization was conducted for 158 customers, with women comprising 65.82%, along with the documentation of 41 waste categories complete with prices and statuses, which improved transaction accuracy and service speed. The success of the program was influenced by the active participation of the management team, strong motivation among women’s groups, and the availability of digital devices. However, challenges were still encountered, especially those related to variations in digital literacy and network constraints. Therefore, further development was recommended through digital capacity-building training, strengthening network infrastructure, and expanding women’s empowerment in waste sorting and recycling-based entrepreneurship. With continuous monitoring, the application was expected to serve as a model for adaptive and sustainable technology-based waste bank management at the village level.